MODEL OF PSYCHOLOGICAL MICRO FOUNDATIONS OF CSR IN CZECH BREWERY - Simona Činčalová; Veronika Toporová (Copernican Journal of Finance & Accounting, 2022)
Corporate Social Responsibility (CSR) is a term that is being defined very diversely. The goal of this research is to show how corporate social responsibility (CSR) is actually implemented and managed in business practice by the Czech brewery. The special emphasis is placed on employees, because they are the key to the company. The method chosen for the research is the micro-level analysis of employee perceptions, reactions, and attitudes towards the company’s CSR together with their determinants. The Model of psychological micro-foundations of CSR is used and, furthermore, the level of administrative employee CSR engagement in the CSR of a Czech brewing company is analyzed. The results show the determinants of this engagement or disengagement, the respondents’ perceptions and evaluation of the company’s CSR and finally, what are the outcomes of their reactions to the CSR of the company.